To increase the responsibility of small businesses in the areas of economic development. - Бейсебаева, С. А. (Journal of Economic Research & Business Administration, 2015)
This article examines the role of the value of regional small business described in the full responsibility . During the analysis , the author Mp active jumılğandardıñ active subjects , as well as small businesses in regions of the Republic of Kazakhstan to the results on the product caused by the proposals to improve the activities of the MP